2022
DOI: 10.22373/sjhk.v6i2.13882
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance Rights of Women in Makassar Society: A Study of Living Qur’an and its Implications for Islamic Law

Abstract: The division of inheritance is one of the main problems in Islamic law. The legal basis for inheritance division refers to the Qur’an and hadith as the sources of law. However, there are different interpretations and practices in society regarding the division of inheritance for women and men. Here, this paper examines the practice of dividing the inheritance of women and men with the living Qur’an approach, and also maps out the forms of reception that occur in society and its implications for Islamic law. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Problem-solving can be done by deliberation to reach a consensus. 61 Allah is wise and knows everything that has happened and will happen, and all conditions whenever and wherever, including the condition of women at the time the verse was revealed and at the present according to the area.…”
Section: Reconstruction Of Understanding Of Biased Verses Of the Al-q...mentioning
confidence: 99%
“…Problem-solving can be done by deliberation to reach a consensus. 61 Allah is wise and knows everything that has happened and will happen, and all conditions whenever and wherever, including the condition of women at the time the verse was revealed and at the present according to the area.…”
Section: Reconstruction Of Understanding Of Biased Verses Of the Al-q...mentioning
confidence: 99%
“…Overall, the feminist perspective on Islamic inheritance law underscores the need for inheritance compared to men, both in terms of quantity and quality of assets. 15 Additionally, research on women's roles in inheritance distribution has shown that women are often less involved in the inheritance distribution process, and the inheritance they receive is often lower than that received by men. 16 The existence of negative perceptions surrounding Islamic inheritance law can impact its reception and comprehension within society.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the author concludes that rajah pelaris is used by the perpetrators to sell their merchandise (Muhammad, 2019). Therefore, the practice of traders using rajah as a rainmaker with Qur'anic verses is called the practice of Living Qur'an (Hamidullah, 2018;Saifuddin, 2019;Halimah et al, 2022;Edward et al., 2022;Zakiyah, 2023).…”
Section: Introductionmentioning
confidence: 99%